Immediate postpartum family planning utilization and its associated factors among postpartum women in Ethiopia: a systematic review and meta-analysis - Silesh, Mulualem; Demisse, Tesfanesh Lemma; Taye, Birhan Tsegaw; Moltot, Tebabere; Chekole, Moges Sisay; Wogie, Girma; Kasahun, Fetene; Adanew, Solomon (Frontiers in Global Women's Health, 2023)
Postpartum women have a greater unmet need for contraceptives compared to non-postpartum women. Immediate Post-partum family planning (IPPFP) is an integrated service and opportunities exist for women by providing FP counseling and contraceptive as part of care following childbirth within 48 hours.